The impact of the gospel on Kariwari-Kenewa culture in Papua - Patasik, Serli (KURIOS, 2023)
Culture concerns the whole life of people who live and practice what they see as the more horizontal dimension; however, no one can be separated from the cultural dimensions. The friction between culture and religion, as a result, encounters problems. On that situation, the current research about Gospel and Kariwari - Kenewa culture is conducted. It focuses on coaching the young generation as successor-centered culture in Kariwari, Papua. At the same time, Kenewa is music bamboo that has mystical strength. The goal of this research is that the tribe who conducts the activities might be released from evil and live in Gospel.